اثر تطبيق المعايير المحاسبية الدولية للقطاع العام في تعزيز الشفافية والمساءلة - مريم, بليله; أماني, مسعودي; ماريا, بيوضة (جامعة الوادي - University of Eloued, 2023)
" هدفت الدراسة إلى إبراز الإطار النظري للمحاسبة العمومية وكذا المعايير المحاسبية الدولية للقطاع العام وأثر تطبقها في تعزيز الشفافية وتحقيق المساءلة، بهدف الحفاظ على المال العام ومواكبة النمو والتطور الاقتصادي. تمت الدراسة من خلال محاولة الإجابة على الإشكالية الرئيسية التالية: ما مدى مساهمة تطبيق المعايير المحاسبية الدولية للقطاع العام في تعزيز الشفافية والمساءلة؟ لمعالجة الموضوع تم الاعتماد على مناهج بحثية، حيث تم الاعتماد على المنهج الوصفي في الجانب النظري حيث تم جمع معلومات وبيانات من مختلف المصادر والمراجع من اجل التعرف على الإطار العام للمعايير المحاسبية الدولية للقطاع العام، وأثر تطبيق هذه المعايير على تعزيز الشفافية والمساءلة وأهمية كل منها، كما تم التطرق إلى النظام المحاسبي العام وكيف تم تطوره اعتمادا على المعايير IPSAS؛ أما في الجانب التطبيقي فقد تم اعتماد المنهج الوصفي التحليلي من خلال جمع البيانات وتحليلها وتفسيرها والوقوف على دلالاتها باستخدام الأدوات والبرامج الإحصائية من أجل التوصل إلى معرفة دقيقة وتفصيلية حول مشكلة الدراسة، تمثلت أداة الدراسة في استبيان موزع على عينة من 103 فرد من محاسبين عموميين وآمرين بصرف وأعوان الرقابة المالية في ولاية الوادي، وقد تم التوصل إلى أن هناك درجة عالية من الوعي بمزايا تطبيق المعايير المحاسبية الدولية للقطاع العام وأثرها في تعزيز الشفافية وتحقيق المساءلة، إذ تبين قصور كل منها في مؤسسات القطاع العام، وتحديات التي تواجهها تبني المعايير المحاسبية الدولية للقطاع العام، لذلك توصي الدراسة بضرورة تحديث النظام المحاسبي بما يدعم ويعزز المساءلة والشفافية ليلائم البيئة وطبيعة النظام السياسي والاقتصادي في الجزائر، وذلك بالاعتماد على معايير المحاسبة الدولية في القطاع العام. " " The study aimed to highlight the theoretical framework of public accounting as well as the International Public Sector Accounting Standards and the impact of their application in enhancing transparency and achieving accountability, with the aim of preserving public money and keeping pace with economic growth and development. The study was conducted through an attempt to answer the following main problem: What is the extent of the contribution of applying international accounting standards for the public sector in enhancing transparency and accountability? Addressing the topic, research methods were relied on, where the descriptive approach was relied on in the theoretical aspect, where information and data were collected from various sources and references in order to identify the general framework of international accounting standards for the public sector, and the impact of applying these standards on enhancing transparency and accountability and the importance of each. The general accounting system and how it was developed based on IPSAS standards were also discussed. On the applied side, the analytical descriptive approach was adopted by collecting data, analyzing and interpreting it, and finding out its implications using statistical tools and programs in order to reach accurate and detailed knowledge about the problem of the study. And the agents of financial control in the state of the Valley, and it was concluded that there is a high degree of awareness of the advantages of applying international accounting standards for the public sector and its impact on enhancing transparency and achieving accountability, as it shows the shortcomings of each of them in public sector institutions, and the challenges they face in adopting international accounting standards for the public sector Therefore, the study recommends the need to modernize the accounting system in a way that supports and enhances accountability and transparency to suit the environment and the nature of the political and economic system in Algeria, based on international accounting standards in the public sector. "
Keywords: معايير المحاسبة الدولية في القطاع العام، القطاع العام، المحاسبة العمومية، الشفافية والمساءلة; international accounting standards in the public sector, public sector, public accounting, transparency and accountability.